Firms' Global Engagement and Management Practices - Holger Görg; Aoife Hanley (Kiel Centre for Globalization (KCG), 2017)
We investigate whether firms' "global engagement", either in the form of exporting or opening up affiliates abroad, is related to the change in their management performance. We use new and unique data from a recent large scale firm survey of management practices in Germany. We calculate management scores for firms as in Bloom et al. (2013), which indicate how structured management is in a given firm. We find that switching into exporting, and to a lesser degree opening up affiliates abroad, is related to improving management performance in the sense of having more structured management practices.
Keywords: F2; L2; M2; 330; Management practices; global engagement; exporting; outward investment